2011
DOI: 10.1116/1.3545808
|View full text |Cite
|
Sign up to set email alerts
|

Collective buckling of line arrays created by soft lithography

Abstract: The authors analyze the collective buckling of an array of elastic lines with their lower edges built into an elastic substrate of the same material. These lines can interact among themselves through the deformation of the substrate. From the theory of elasticity and elastic structures, an eigenvalue problem is formulated and solved. Calculations show that the lines can buckle collectively into certain ordered patterns, where some of which have been confirmed by experiments. The results are useful for the unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Substrate deformation leads to coupling between lines which results in collective buckling. 6 In our case, the same mechanism can explain the collective lines buckling observed in Figure 3. Figure 4 represents a superposition of the simulation and experimental results previously described for line wiggling for different titanium nitride residual stress as a function of the line dimension.…”
supporting
confidence: 77%
“…Substrate deformation leads to coupling between lines which results in collective buckling. 6 In our case, the same mechanism can explain the collective lines buckling observed in Figure 3. Figure 4 represents a superposition of the simulation and experimental results previously described for line wiggling for different titanium nitride residual stress as a function of the line dimension.…”
supporting
confidence: 77%
“…In the experiments, collective bulking of nanopillar arrays was explored to promote for nanolithography [Zhang et al, 2006;Lin et al, 2007]. Corresponding numerical analysis showed that the surface pattern of structures was regulated by varying gravitational potential energy of columns [Chen et al, 2008[Chen et al, , 2011Lin et al, 2010;Li et al, 2012].…”
Section: Introductionmentioning
confidence: 99%